2006
DOI: 10.1007/s00249-006-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional asymmetry of transmembrane segments in nicotinic acetylcholine receptors

Abstract: Nicotinic acetylcholine receptors are heteropentameric ion channels that open upon activation to a single conducting state. The second transmembrane segments of each subunit were identified as channel-forming elements, but their respective contribution in the gating process remains unclear. Moreover, the detailed impact of variations of the membrane potential, such as occurring during an action potential, on the transmembrane domains, is unknown. Residues at the 12¢ position, close to the center of each second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
3
5
1
Order By: Relevance
“…Furthermore, the quaternary twist motion is highly symmetric in the pore region and involves all subunits equally. This is in contradiction to some experimental data indicating a strongly nonequivalent contribution of different subunits to gating 25, 27…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the quaternary twist motion is highly symmetric in the pore region and involves all subunits equally. This is in contradiction to some experimental data indicating a strongly nonequivalent contribution of different subunits to gating 25, 27…”
Section: Resultscontrasting
confidence: 99%
“…Previous reports already suggested that when the nature of a gate is hydrophobic instead of geometric occlusion, the required pore widening may be smaller than that commonly assumed 31, 70, 73. In addition, asymmetry of the conformational changes in our model correlates with experimental findings on the unequal contributions from different subunits to the gating movement 25, 27…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…52,53 Experimental data also support the role of asymmetric motion in channel functions. 56,57 An asymmetric and independent contribution of the TM2 residues to gating of nAChR was observed in a single-channel study. 56 Thus, it is not surprising to see spontaneous asymmetric motion in our simulations.…”
Section: Resultsmentioning
confidence: 91%
“…Details of the synthesis (Scheme 1) of fluorescent EPB ligands and all other experiments are provided in the Supporting Information and also in references [22][23][24] for radioligand competition and protection binding experiments, in references [25][26][27] for expression and electro- …”
Section: Methodsmentioning
confidence: 99%